Characterization of Ag-Doped p-Type SnO Thin Films Prepared by DC Magnetron Sputtering. (18th December 2017) - Pham, Hoai Phuong; Thuy, Thanh Giang Le; Tran, Quang Trung; Nguyen, Hoang Hung; My Hoa, Huynh Tran; Thi Thu, Hoang; Cuong, Tran Viet
Abstract : Crystalline structure and optoelectrical properties of silver-doped tin monoxide thin films with different dopant concentrations prepared by DC magnetron sputtering are investigated. The X-ray diffraction patterns reveal that the tetragonal SnO phase exhibits preferred orientations along (101) and (110) planes. Our results indicate that replacing Sn 2+ in the SnO lattice with Ag + ions produces smaller-sized crystallites, which may lead to enhanced carrier scattering at grain boundaries. This causes a deterioration in the carrier mobility, even though the carrier concentration improves by two orders of magnitude due to doping. In addition, the Ag-doped SnO thin films show a p-type semiconductor behavior, with a direct optical gap and decreasing transmittance with increasing Ag dopant concentration.